ETHNIC AND POLITICAL CONSTITUENTS OF NATIONAL IDENTITY (Heritage, 2022)
The collapse of the Soviet Union and the eastern socialist lager, and then the disintegration of Socialist Yugoslavia, which was followed by strong ethnic antagonisms, whose cruelest form was an armed struggle, of until then "fraternal" peoples, historically "close", "same", who "achieved full national freedom and equality" in the common state, and pushed the themes of nation and nationalism to the forefront of sociological theory and political practice. Basic theoretical and research approaches to the nation in sociology, developed especially in the West, "liberated" the field of social sciences in the countries of the former socialist East, Marxist and communist theories about the nation and the national question.Moreover, not even the renewed studies of "nation and nationalism" have fully introduced conceptual and theoretical coherence in their research field, on the contrary, the increased interest in the topics of nation and nationalism, which followed in the second half of the last century and at the beginning of this century, led to even greater "incomprehensibility" and the existing ambiguities in the conceptual and theoretical sense have not decreased.In this paper, we deal with the problems of the "new incomprehensibility", which some authors called "terminological jungle", "conceptual anarchy" when defining and demarcating the basic terms in the field of nation and nationalism and related terms.We tried to determine when a nation is created and what are the constitutive elements of a nation and national identity. The postulates of the primordialist and ethno-symbolist direction in the research of the nation and nationalism are dominant in the understanding of the nation in the post-Yugoslav area and as such have been confirmed in practice, which once again dealt a blow to the theory of the "end of nations" and pan-nationalism, which came to life only within the framework of scientific works.
Keywords: Ethnic communities, ethnicity, ethnic and political nation, state and citizenship, national identity